Destination Development Hot Water Bath Sapan Sapan Maluluang Village District Pauah Duo Southern District Solok - Gusriani, Rika - (STKIP PGRI Sumbar, 2014)
This study aims to determine the development of Thermal Baths Attractions in the Village Sapan Maluluang Pauh Duo Sapan District of South Solok can be seen: 1) Accessibility Sapan Maluluang Thermal Baths in the Village District of Pauh Sapan 2 Duo) Thermal Baths accommodation in the village of Sapan Sapan Maluluang Duo Pauh Subdistrict 3) Guest Thermal Baths Sapan Maluluang Year 2011-2013 in the Village District of Pauh Duo Sapan.This research is qualitative. Data were collected through observation, interviews, photo shoots taken in the field. The validity of the test data using triangulation techniques. Triangulation technique is a technique that utilizes data validity checking something else.The results showed that: 1) accessibility Attractions Thermal Baths Sapan Maluluang contained in District Pauah duo already very smoothly in the absence of obstacles in the road because the road is good, just that there is no public transport that passes through the attractions when there are visitors shall be visited by public transport to attractions Thermal Baths Sapan the Maluluang.2) Accommodation Attractions: Thermal Baths Sapan Maluluang contained in District Pauah inadequate Duo with a lack of hotels surrounding attractions if there are foreign tourists who visit and want to stay.3) Visitor Attractions: Thermal Baths Sapan Maluluang contained in District Pauah duo have started to rise in the previous compare. In 2011 amounted to 13 425 people, in 2012 amounted to 11 078 people, in 2013 amounted to 13 890 people. Its just that in 2012 the number of visitors decreased because in that year attractions are under construction.